Analysis of Increasing Revenue on Seasonal Wedding Organizer Products in Batujaya District - Mutiara Ramadhini; Dedi Mulyadi; Santi Pertiwi Hari Sandi (West Science Business and Management, 2024)
This research was conducted with the aim of knowing how to increase income during the seasonal period at Apri Decoration Wedding Organizer. This research was conducted in October 2022 - November 2023 in Batujaya District with the object being the Apri Decoration Wedding Organizer. Apri Decoration Wedding Organizer offers wedding organizer services to organize various series of wedding events providing special services in the field of marriage. The research method used is the Qualitative Descriptive method. Data collection is done by interview and observation. Based on the results of the study in 2023 the highest income occurred in May-June (Syawal-Dzulhijah) with a percentage of 20.2%, this is due to entering the Islamic month, so there is a lot of demand for the use of Wedding Organizer services.  The highest decrease in revenue was 90.9% in August-September (Muharram-Safar) this is because the Muslim community believes that the month is not to hold a wedding, which is recommended by the Prophet. To anticipate this in order to continue to increase and its income also continues to rise, what Apri Decoration Wedding Organizer does is to give confidence to consumers through payment with a DP (Down Payment) system or down payment first, and it is not determined how much down payment must be paid. Then consumers can also use wedding services in advance without providing payment (debt) or down payment, and make payments if the event has been completed. Based on the results of research on how to increase revenue carried out by Apri Decoration Wedding Organizer in the form of trust, approach, social media such as Facebook which is usually used to share the results of bridal Make Up, bridal fashion collection models. In addition, Apri Decoration Wedding Organizer also collaborates with other parties or third parties such as mediators, and this really helps business owners to continue to earn income when it is not seasonal.